Self-assembled impurity and its effect on magnetic and magnetocaloric properties of manganites. Issue 14 (1st October 2018) - Mohamed, Abd El-Moez A.; Hernando, B.
Abstract: This work investigates the effect of self-assembled impurities on magnetic and magnetocaloric properties of the La0.3 Ba0.7 MnO3 and the La0.3 Sr0.7 MnO3 compounds. The x-ray diffraction patterns show multiple secondary phases in the as prepared conditions due to the incomplete interaction among reactants. However, the homogeneity is enhanced gradually by increasing the sintering temperature until a high purity phase is obtained at the 1200 °C sintering temperature. Results show that the magnetic and the magnetocaloric properties are promoted with the homogeneity and sintering temperature, where there is a monotonic increase in the saturation magnetization and the Curie temperature with the increase of sintering temperature. In addition, the magnetic entropy change of the La0.3 Sr0.7 MnO3 compound increases from 0.1 J/kgK for the as prepared condition to 0.2 J/kg K and 0.8 J/kg K for the 800 °C and the 1200 °C sintering temperatures, respectively. And for the La0.3 Ba0.7 MnO3 compound, the magnetic entropy change shows the values of 0.35 J/kg K and 0.78 J/kg K for the 800 °C and 1200 °C sintering temperatures respectively.